2002
DOI: 10.1097/00007890-200211150-00013
|View full text |Cite
|
Sign up to set email alerts
|

Humorally mediated posttransplantation septal capillary injury syndrome as a common form of pulmonary allograft rejection: a hypothesis

Abstract: Septal capillary injury accompanied by direct and indirect immunofluorescent evidence of humoral immunity is a frequent finding on transbronchial biopsies. The findings suggest that humoral immunity to endothelial-based alloantigen is a common occurrence in lung grafts and may be a critical factor in chronic graft dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
82
2
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 20 publications
1
82
2
2
Order By: Relevance
“…We have recently shown a role for humoral immunity in the propagation of acute and chronic lung graft dysfunction (1). Features of the acute syndromic complex are those of dyspnea, fever, and lung infiltrates, while light microscopically there is evidence of a necrotizing septal capillary injury syndrome accompanied by immunoreactant deposition within the interalveolar septal capillaries (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shown a role for humoral immunity in the propagation of acute and chronic lung graft dysfunction (1). Features of the acute syndromic complex are those of dyspnea, fever, and lung infiltrates, while light microscopically there is evidence of a necrotizing septal capillary injury syndrome accompanied by immunoreactant deposition within the interalveolar septal capillaries (1).…”
Section: Introductionmentioning
confidence: 99%
“…Features of the acute syndromic complex are those of dyspnea, fever, and lung infiltrates, while light microscopically there is evidence of a necrotizing septal capillary injury syndrome accompanied by immunoreactant deposition within the interalveolar septal capillaries (1). In patients fulfilling the criteria for bronchiolitis obliterans syndrome (BOS), the prototypic cause of chronic lung graft dysfunction, bronchial wall immunoreactant deposition with localization to the bronchial epithelium and microvasculature of the bronchial wall has also been recently identified (2).…”
Section: Introductionmentioning
confidence: 99%
“…4,9,10 However, it is important to note that the use of C4d as a surrogate marker for development of DSAs and subsequent AMR in lung has shown conflicting results. [11][12][13][14][15][16][17][18][19][20] Some studies have shown a correlation between the presence of DSAs and C4d deposition in lung allografts but others have not. 11,17,20 It is critical to correctly identify patients with AMR because the development of anti-HLA alloantibody has been shown to be a major risk factor for poor outcomes in lung transplants.…”
mentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20] Some studies have shown a correlation between the presence of DSAs and C4d deposition in lung allografts but others have not. 11,17,20 It is critical to correctly identify patients with AMR because the development of anti-HLA alloantibody has been shown to be a major risk factor for poor outcomes in lung transplants. 21,22 Additionally, the development of anti-HLA DSAs is associated with high-grade acute cellular rejection (ACR), lymphocytic bronchiolitis, bronchiolitis obliterans syndrome, and increased use of immunosuppressive therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation